Corrigendum to “Enhanced grain growth and dielectric properties in aerosol deposited BaTiO3” [J. Eur. Ceram. Soc. 43 (2023) 4386–4394, (S0955221923001929), (10.1016/j.jeurceramsoc.2023.03.012)] - Bentzen, Marcus; Maier, Juliana; Eckstein, Udo; He, Jianying; Henss, Anja; Khansur, Neamul Hayet; Glaum, Julia (Journal of the European Ceramic Society, 2023)
The authors regret the error in the acknowledgment section. The following text provides the missing funding information “Juliana Maier, Udo Eckstein, and Neamul Khansur gratefully acknowledge the financial support for this work from the Deutsche Forschungsgemeinschaft under GRK2945/F”. The authors would like to apologise for any inconvenience caused.
CRIS-Team Scopus Importer:2023-09-01

Effect of A-site non-stoichiometry in NaNbO3 ceramics - Hussain, Ali; Gadelmawla, Ahmed; Maier, Juliana; Eyoum, Gina; Miyazaki, Hidetoshi; Kimura, Koji; Hayashi, Koichi; Webber, Kyle Grant (Scripta Materialia, 2025)
NaNbO3 (NN) is a potentially promising material for energy storage and conversion. Understanding the structure-property relationships of NN is crucial for its precise development and implementation in various devices. This work reports the effect of Na non-stoichiometry on structure and ferroelectric properties of polycrystalline NN ceramics. Slight deviations of Na content in NN were observed to create large variations in microstructure, such as grain morphology and reduction in grain size. An insignificant phase change is observed in x-ray diffraction analysis; however, the pair distribution function (PDF) results show a nonuniform atomic displacement which are not directly observed by standard crystallographic techniques. A small amount of Na excess (2 mol.%) in NN enhanced the dielectric constant, polarization, and strain response, whereas a deficiency of same amount degrades electromechanical performance. This work not only explores Na non-stoichiometric effect in NN, but also provides a pathway for development of high performance NN-based ceramics.
CRIS-Team Scopus Importer:2024-10-04
Keywords: Antiferroelectric; Dielectric; Ferroelectric; NaNbO; Structure

Electromechanical properties of paper-derived potassium sodium niobate piezoelectric ceramics - Wahl, Larissa; Maier, Juliana; Schmiedeke, Samuel; The-An Pham; Fey, Tobias; Webber, Kyle Grant; Travitzky, Nahum; Khansur, Neamul Hayet (Journal of the American Ceramic Society, 2022)
The small-signal dielectric and piezoelectric coefficients of paper-derived sodium potassium niobate, K0.5Na0.5NbO3 (KNN), were compared with those of conventionally prepared samples. Results show similar functional properties of paper-derived KNN without significantly decreasing the small-signal piezoelectric coefficient. The structure and microstructure analysis of conventional KNN and paper-derived KNN did not reveal any significant difference in the crystal structure and grain size. However, the temperature-dependent inter-ferroelectric phase transition temperature estimated from the temperature-dependent dielectric permittivity data revealed a decrease of approximately 18°C for the paper-derived KNN and is possibly associated with the structural and microstructural defects. This work indicates that optimizing suspension chemistry and sintering conditions will be critical to enhance the functional response of paper-derived KNN further. Moreover, paper-derived ceramic processing, a novel and cost-effective additive manufacturing technology, can be potentially used to fabricate other electroceramics with a wide range of porosities and sizes as well as complex geometries and multilayer structures.
CRIS-Team Scopus Importer:2022-08-05
Keywords: KNN; lead-free ferroelectrics; paper-derived ceramics; piezoelectrics

Enhanced grain growth and dielectric properties in aerosol deposited BaTiO3 - Bentzen, Marcus; Maier, Juliana; Eckstein, Udo; He, Jianying; Henss, Anja; Khansur, Neamul Hayet; Glaum, Julia (Journal of the European Ceramic Society, 2023)
Piezoelectric ceramics are envisioned as cell stimulating materials for in-vivo, load-bearing applications. To compensate for their brittle nature developing ceramic films on medically accredited metals is a promising approach. However, high temperature consolidation is often required to achieve highly dense ceramics with suitable functional properties, which can compromise the metal substrate integrity. With aerosol deposition highly dense thick films can be produced at room temperature. Still, an annealing step is required to enhance the functional properties of piezoelectric ceramics. Thermal annealing of dense, aerosol deposited BaTiO3 thick films on 304SUS stainless steel gave a clear enhancement of the dielectric properties. An increase in saturation polarization and the adoption of ferroelectric hysteresis at 750 °C coincided with a significant reduction in mechanical properties. The simultaneous appearance of grain growth and diffusion of chromium from the substrate at 750 °C suggests that chromium acts as a sintering aid.
CRIS-Team Scopus Importer:2023-04-14
Keywords: Aerosol deposition; Barium titanate; Functional ceramics; Sintering; Thick films

Influence of grain size on electromechanical properties of (Ba,Ca)(Zr,Ti)O3: A multiscale analysis using spark plasma sintering and aerosol deposition - Maier, Juliana; Kuhfuß, Michel; Urushihara, Daisuke; Gadelmawla, Ahmed; Khansur, Neamul Hayet; Hall, David; Algueró, Miguel; Martin, Alexander; Kakimoto, Ken ichi; Webber, Kyle Grant (Ceramics International, 2024)
The piezoelectric and ferroelectric properties of aerosol deposited (AD) thick ceramic films are significantly reduced in comparison to bulk materials, which is assumed to be largely related to the nanometer-sized grains (∼0.01 μm) observed in the resulting microstructures. This work, therefore, focuses on understanding the role of grain size in electromechanical properties within the range of AD films based on Ba0.85Ca0.15Zr0.1Ti0.9O3 (BCZT). In a comprehensive compilation of the piezoelectric constant (d33) of samples from various studies the grain size dependency of the d33 was shown for the lead-free ferroelectrics BCZT, BaTiO3, and (K,Na)NbO3. In this, it can be seen that no BCZT sample with a grain size below 0.4 μm was analyzed regarding their d33 before, thereby leaving a gap to the grain size of AD films. In this study, the grain size of ceramic bulk samples was varied using spark plasma and conventional sintering (0.1 μm – 11 μm) and their properties compared to those of AD films. To enable the fabrication of bulk samples in the same range as AD films, a hydrothermal powder with an average particle size of 0.075 μm was synthesized. A continuous increase of the permittivity, the polarization, and the piezoelectric coefficient was observed through grain size increase. These results suggest that the grain size of AD films needs to be enhanced to improve their properties. Importantly, the insights of this multiscale analysis on the grain size can help to tailor also the properties of other BCZT films and bulk samples.
CRIS-Team Scopus Importer:2024-06-14
Keywords: Aerosol deposition; Barium calcium zirconium titanate; Grain size; Lead-free; Spark plasma sintering; Synchrotron

In situ electric field-dependent structural changes in (Ba,Ca)(Zr,Ti)O3 with varying grain size - Kuhfuß, Michel; Maier, Juliana; Hall, David A.; Xie, Bingying; Kleppe, Annette K.; Martin, Alexander; Kakimoto, Ken Ichi; Khansur, Neamul Hayet; Webber, Kyle Grant (Journal of Applied Physics, 2024)
The functional properties of piezoelectric ceramic materials, such as barium titanate, are highly dependent on grain size. Lead-free polycrystalline Ba0.85Ca0.15Zr0.1Ti0.9O3 (BCZT) samples were prepared with a combination of the hydrothermal method and spark plasma sintering to achieve grain sizes from 100 nm to 10 μm by varying the maximum sintering temperature. In this range, a transition from a nearly linear dielectric to a ferroelectric response can be seen in macroscopic electromechanical measurements, demonstrating the importance of grain size on functional properties in BCZT. Furthermore, in situ electric field-dependent synchrotron x-ray diffraction measurements were performed to quantify the intrinsic and extrinsic strain contributions and their variations with grain size. At lower grain sizes, the data revealed a significant loss of extrinsic contributions in the piezoelectric behavior, limiting the response to intrinsic contribution associated with lattice strain. For BCZT, a critical grain size between approximately 0.08 and 0.18 μm is proposed, below which no piezoelectric response was observed.
CRIS-Team Scopus Importer:2024-05-17

Investigating the importance of strain-coupling in lead-free 2-2 relaxor/ferroelectric composites with digital image correlation - Martin, Alexander; Maier, Juliana; Streich, Friedemann; Kamlah, Marc; Webber, Kyle Grant (Smart Materials & Structures, 2022)
Ceramic-ceramic composite structures are a viable solution to improve the electromechanical response of lead-free ferroelectrics (FEs) through tuning of the local electrical and mechanical fields. The origin of the enhanced properties, however, remains unclear, as many of the possible effects, such as polarization and strain coupling (PSC) as well as interface diffusion, are interrelated and difficult to separate or directly investigate. In this study, we use a custom-built digital image correlation system to directly investigate the influence of strain coupling on 2-2 composites consisting of 0.90Na(1/2)Bi(1/2)TiO(3)-0.06BaTiO(3)-0.04K(0.5)Na(0.5)NbO(3) (NBT-6BT-4KNN) and 0.94Na(1/2)Bi(1/2)TiO(3)-0.06BaTiO(3) (NBT-6BT) by varying the mechanical interface contacts between end members. Specifically, two model cases were utilized to separate the relative contributions of the PSC mechanisms: (a) electrically connected and (b) mechanically and electrically connected. The local strain gradient was characterized through the thickness of the composite across different layers as well as the interface, where the macroscopic large signal longitudinal and transverse FE response was determined. Experimental results reveal an enhancement of the large signal piezoelectric coefficient d33* <i by approximately 10% from 390 to 440 pm V-1 due to strain coupling.
CRIS-Team WoS Importer:2022-06-10

Observation of the local electromechanical response in 2-2 ceramic-ceramic lead-free ferroelectric composites via digital image correlation - Martin, Alexander; Maier, Juliana; Kakimoto, Ken Ichi; Kamlah, Marc; Webber, Kyle Grant (Journal of Applied Physics, 2024)
This study investigates bilayers of 0.94(Na1/2Bi1/2)TiO3-0.06BaTiO3 (NBT-6BT) and 0.90(Na1/2Bi1/2)TiO3-0.06BaTiO3-0.04(K0.5Na0.5)NbO3 (NBT-6BT-4KNN) using digital image correlation, enabling the separate analysis of strain response in each layer. The bilayers were electrically connected without mechanical connection (polarization coupled) as well as mechanically and electrically connected (polarization and strain coupled) to determine the role of interlayer mechanical interactions. The large signal longitudinal and transverse piezoelectric coefficients, d 33 ∗ and d 31 ∗ , were characterized for both cases. In the polarization coupled composite, d 33 ∗ decreased linearly from 410 to 260 pm/V with increasing vol. % NBT-6BT. In contrast, in the polarization and strain coupled case, d 33 ∗ and d 31 ∗ were maximum at 50 vol. % NBT-6BT with values of 440 and −130 pm/V, respectively, highlighting the critical role of strain interactions in ceramic-ceramic composites. The stress-induced phase transformation through strain coupling significantly impacted the electromechanical response, with improved strain values observed in the NBT-6BT-4KNN layer. Furthermore, this study highlights the variability in the significance of strain coupling within bilayer systems as a function of the altering volume fraction of their constituent components.
CRIS-Team Scopus Importer:2024-02-16

Stress-induced tailoring of energy storage properties in lead-free Ba0.85Ca0.15Zr0.1Ti0.9O3 ferroelectric bulk ceramics - Maier, Juliana; Gadelmawla, Ahmed; Khansur, Neamul Hayet; Webber, Kyle Grant (Journal of Materiomics, 2023)
In this study, the stress-modulated energy storage properties of lead-free polycrystalline Ba0.85Ca0.15Zr0.1Ti0.9O3 was investigated as a function of temperature from 25 °C to 55 °C. The externally applied uniaxial compressive stress of −160 MPa increased the recoverable energy storage density by 226% to a maximum value of 274 mJ/cm3, in addition to enhancing the energy storage efficiency by approximately 10% to a value of 88.2%. The macroscopic mechanical constitutive behavior is presented as well as the stress-dependent dielectric and ferroelectric properties and the Rayleigh behavior in order to elucidate the effect of stress on the energy storage properties. Importantly, the stress-induced tailoring of energy storage performance can be utilized for other nonlinear dielectric ceramics to tune their extrinsic polarization mechanisms to significantly enhance the recoverable energy density and reduce the hysteretic losses.
Created from Fastlane, Scopus look-up
Keywords: Energy storage; Ferroelectric; Lead-free; Polarization mechanism; Rayleigh behavior; Stress-dependent

The Impact of Grain Growth on the Functional Properties in Room-Temperature Powder Aerosol Deposited Free-Standing (Ba,Ca)(Zr,Ti)O3 Thick Films - Maier, Juliana; Fuggerer, Tim; Urushihara, Daisuke; Martin, Alexander; Khansur, Neamul Hayet; Kakimoto, Ken Ichi; Webber, Kyle Grant (Crystals, 2024)
This study investigates the development of freestanding thick films (FSFs) of lead-free (Ba,Ca)(Zr,Ti)O3 and the role of grain growth on the electromechanical response. During deposition, room temperature powder aerosol deposition rapidly produces thick films with a nano-grain structure that limits the electromechanical properties. In this study, the films are removed from the substrate using a sacrificial buffering layer to avoid thermal treatment and allow for an initial as-processed state. Following this, FSFs were thermally treated at various annealing temperatures from 800 °C to 1400 °C to induce grain growth, which was characterized with scanning and transmission electron microscopy. X-ray diffraction revealed an increase in the crystallite size consistent with an increase in grain size and a decrease in internal residual stress. The temperature-dependent dielectric behavior and the large-field ferroelectric response were also characterized, revealing significant differences of the FSFs from the bulk properties.
CRIS-Team Scopus Importer:2024-05-10
Keywords: BCZT; ferroelectrics; grain growth; lead-free; powder aerosol deposition

The role of Ca/Zr ratio on the local structure and phase transitions in lead-free (Ba,Ca)(Zr,Ti)O3 - Dobesh, David; Gadelmawla, Ahmed; Miyazaki, Hidetoshi; Hinterstein, Manuel; Kimura, Koji; Maier, Juliana; Banerjee, Semanti; Zeair, Omar; Mehta, Sharly; da Silva, Lucas Lemos; Khansur, Neamul Hayet; Hayashi, Koichi; et al. (Journal of the European Ceramic Society, 2024)
In this study, the structural phase transitions are investigated as a function of composition and temperature for polycrystalline x(Ba0.7Ca0.3)TiO3-(1 − x)Ba(Zr0.2Ti0.8)O3 (x = 0.40, 0.45, 0.50, 0.55, and 0.60) through a combination of Raman spectroscopy, synchrotron X-ray diffraction, and dielectric spectroscopy. The aim is to gain insight into the complex phase boundary region responsible for the excellent electromechanical properties. The results demonstrate the correlation between local site substitutions based on the stoichiometric variations to the microstructure and dielectric properties. The dielectric response has been correlated with the BCT/BZT content displaying a maximum depending on the phase content. Additionally, in situ temperature-dependent Raman, permittivity, and pair distribution function (PDF) studies were performed from −60 °C to 130 °C to highlight the structure and phase evolution. In particular, the in situ temperature-dependent Raman measurements reveal sudden discontinuities in the vibrational modes that correspond to the structural changes in the perovskite structure. Therefore, the results of the permittivity response, based on the average of a large volume, are consistent with the local structural changes obtained by other techniques. Indeed, correlations of Raman, X-ray diffraction, and PDFs obtained from synchrotron X-ray total scattering data, along with permittivity measurements allowed the identification of the discrete ferro- to paraelectric phase transitions and a more robust characterization. The rotation and distortion of the octahedral caused by oxygen displacement are driving forces behind symmetry changes and phase transitions, explaining the mechanism of polymorphic phase transition based on A- and B-site substitution. Therefore, this work provides a comprehensive understanding of temperature and composition-dependent phase transitions in BCZ